A Family Law of Contemporary and Possible Weaknesses: Disposal Parental Forward or Backward? - Paiva, Caroline Zanetti (2015)
Hard work is define where and how the family institution had begun. Although it has gone through numerous and constant transformations, family resisted the time and suited the needs of society. The end of patriarchy, equality of rights and duties between men and women, the equitable division of tasks and shared responsibilities entailed numerous benefits to family life and on the other leveraged its fragility. With the contemporary family structure also stemmed the relentless pursuit of individual desire threatening the maintenance of the marriage as well the strengthening of its structure. One of the visible and growing evils in the current  family  is  the  practice  of  Parental  Alienation,  where  the  alienating  performs maneuvers in order to poison the child against the other parent, thus causing serious consequences to their training that are unlikely to be reversed.